Empowering the Community with Briquette Fuel: Utilizing Palm and Sago Waste - Haurissa, Jusuf; Puspita, Gratia Deodata Haruina Dwi; Mini, Marthina; Silak, Kemuel; Wayne, Jefri; Lekatompessy, George (Universitas Serang Raya, 2025)
In Suskun Village, waste from palm oil and sago pulp is abundant. This waste is not only an environmental issue but also a challenge for the local community in terms of management. This community service program aims to train the community in producing briquettes as an environmentally friendly alternative fuel from these waste materials. Additionally, the program seeks to teach the community how to calculate the selling price of briquettes, enabling them to achieve economic independence in running their briquette business. The methods used in this program include: a) Socialization on briquette production from palm oil and sago pulp waste, b) Training on briquette-making through practical workshops, c) Implementation of technology by the community, d) Assistance and evaluation of the briquette production process, e) Sustainability of the program as a briquette business for the Suskun Village community, and f) Active community participation in all program stages. Throughout the activity, mentoring and evaluation of production outcomes were conducted to ensure the sustainability of the briquette business, allowing it to grow into a viable enterprise for the community. This program has yielded positive results, as the community can now independently produce briquettes from palm oil and sago pulp waste. This initiative creates economic opportunities and helps reduce waste in Suskun Village.